Secure E-government web services - Mitrakas, Andreas (Hershey PA : Idea Group Pub., 2007)
"This book addresses various aspects of building secure E-Government architectures and services; it presents views of experts from academia, policy and the industry to conclude that secure E-Government web services can be deployed in an application-centric, interoperable way. It addresses the narrow yet promising area of web services and sheds new light on this innovative area of applications"--Provided by publisher.
Includes bibliographical references and index.
Keywords: Electronic government information -- Security measures -- United States; Internet in public administration -- United States; Electronic government information -- United States